Salsa dancing into the social sciences : research in an age of info-glut - Luker, Kristin (Harvard University Press, 2008)
"This book is both a handbook for defining and completing a research project, and an astute introduction to the neglected history and changeable philosophy of modern social science."--Provided by publisher